TEACHING LEGAL DISCIPLINES IN NON-LEGAL INSTITUTIONS OF HIGHER EDUCATION - Закревская, Анна (SWorldJournal, 2022)
The question of necessity of increase of amount of educational o'clock of for teaching of legal disciplines in insti- tutes of higher of unlegal direction, which contact with the requirements of today, is examined: tacking to European educational space,